PERBANDINGAN IMPLEMENTASI ISO DAN PELUNCURAN ENTERPRISE RESOURCES PLANNING TERHADAP INDEKS KINERJA KEUANGAN - Sautma Ronni Basana (Jurnal Keuangan dan Perbankan, 2011)
Recently, companies implemented projects which applied on companies overall system. These recent bestpractices of pursuing companies effectiveness and efficiency would be implementation of ISO 9000 and ERP.Previous research showed that these two projects could bring benefits for these companies which implementedit. However, it had not been compared which project would bring more benefits to these companies. Thisresearch observed 35 companies which consisted of 15 companies in food and beverages industry, 9 companiesin pharmaceutical industry, 4 companies in cigarettes industry, 4 companies in cosmetics industry, and 3companies in household appliances industry. The data were taken by observing and recording the valueswhich related to COGS (cost of goods sold), total inventory, net income, gross income, operating income, pretaxincome, cash flow operation, total liabilities, and total asset after ISO and ERP implementation. The resultsshowed that there was no significant difference of the ISO and ERP implementation on the factors of inventoryturnover, and weeks of supply. While the other factors showed significant differences between the implementationof ERP and ISO. Net profit margin, gross profit margin, and operating profit margin showed better resulton ERP launching. On the other hand, pretax margin showed better than ISO 9000 implementation. Overall,ERP implementation showed better results compared with ISO 9000.